The Determinants Of Long And Medium Haul International Tourists’ Length Of Stay In Malaysia - Tay, Kai Xin (2018)
Tourism is becoming an increasingly important contributor to the Malaysia economy. However, it has been acknowledged as a problem that the growth of tourism industry in Malaysia is due to tourist arrivals but not the receipt per arrival. This is because lower average length of stay. Tourists who stay at one destination longer means visit more attractions and generate more businesses for the destination. The theory of planned behaviour was used to understand the determinant factors of tourists’ length of stay in Malaysia. To be exact, this thesis aims to study marketing mix, attitude, subjective norm, and perceived behavioural control toward the formation of tourists’ length of stay in Malaysia. It also aims to identify the impact of marketing mix on the formation of attitude and investigate the moderate effects of different age groups and travel distance on these determinants toward the length of stay in Malaysia. Three main hypotheses were outlined. A pilot study with 55 respondents was performed using Stata14.2 software to ensure the validity and reliability of the proposed test model. After the pilot study, the revised questionnaire was used in the final data collection with 384 respondents at five Malaysia International Airports. Descriptive analysis and survival analysis were applied and the thesis findings revealed that the theory of planned behaviour was better in predicting international tourists’ length of stay in Malaysia. The results showed that mediated relationship of marketing mix and attitude was generally much more important than as independent variables toward length of stay. On the other hand, moderated relationship of age and travel distance was also proven and this finding was crucial to destination marketers in term of market segmentation and in designing marketing mix. The theoretical and practical implications of the study were discussed followed by research limitation and future direction.